ABNORMAL RETURN DAN VOLATILITAS INDEKS HARGA SAHAM GABUNGAN PADA PASAR EKUITAS NEGARA ASEAN 5 SELAMA PANDEMI COVID-19 - Disya Seviana Putri; Ossi Ferli (Journal of Accounting, Management and Islamic Economics, 2025)
World financial markets, particularly stock exchanges, have been affected by COVID-19. Marked by the Composite Stock Price Index (IHSG) of global exchanges which simultaneously decreased during the pandemic. This study aims to determine the difference between Abnormal Return before and after the annooncement of Covid-19 by WHO and to determine the JCI volatility on the equity markets of ASEAN 5 countries during the Covid-19 pandemic. The sample used is the closing price of the ASEAN 5 daily global stock price index using the MSCI index via the investing.com website. This study uses a descriptive analysis method approach, with event study, GARCH and regression methods. The research period for abnormal returns was the closing price of the JCI at t-10, 1 day at the time of the announcement and t+10 and JCI volatility on March 12 2020- December 12 2022. The results showed that there were significant differences in abnormal returns before and after the announcement of Covid-19 by WHO in ASEAN 5 countries. Previous volatility had an effect on current volatility, and JCI volatility had a positive effect on abnormal returns during the Covid-19 period in ASEAN 5 countries.